Comparative analysis of radiocephalic versus brachiocephalic native arteriovenous fistula for hemodialysis in end stage renal disease - Khadatkar, Aniket; Mahakalkar, Chandrashekhar; Pradhan, Tanu; Bora, Akshay (International Journal of Research in Medical Sciences, 2016)
Background: Chronic kidney disease (CKD) is a long term condition caused by damage to both kidneys. The benefits of arteriovenous fistulas over other forms of chronic access are: Arteriovenous fistulas are associated with decreased morbidity and mortality among hemodialysis patients compared with arteriovenous grafts and central venous catheters. Objectives of the study were o choose the proper sites for formation of arteriovenous fistula, to find out the success rate at various sites and to study the complications of arteriovenous fistula. Methods: This prospective study was carried out on total 150 patients over the duration of two years. The fistulae were created using radial artery and cephalic vein side to side (Radiocephalic AVF) and brachial artery and cephalic vein side to side anastomosis (Brachiocephalic AVF). Doppler studies were done before and after every procedure to demonstrate the velocity, volume of blood flow, depth from the skin, diameter of vessels and to access the time of maturation of AVF. Patients were followed up to first dialysis by AVF to assess the overall outcomes and various complications. Results: Brachiocephalic AVF matured earlier than Radiocephalic AVF (mean maturation time Brachiocephalic 38.02 days and Radiocephalic 43.26 days) which was statistically significant. Brachiocephalic AVF matured earlier than Radiocephalic AVF with more flow rate. Complication rate was more at wrist (Radiocephalic AVF with 66.67% of overall complication) than at elbow (Brachiocephalic AVF with 33.33% of overall complication). Conclusions: We concluded that the Brachiocephalic AVF maturation time was significantly less than the maturation time of Radiocephalic AVF and rate of complication was less in Brachiocephalic AVF. The utility of pre-operative colour Doppler to select the vessels for AVF creation was found to be as an essential parameter of pre-operative work up.